ANALISIS STATISTIK LEVEL DAYA SINYAL PROVIDER TELKOMSEL DAN XL DI JURUSAN TEKNIK ELEKTRO UNIVERSITAS MATARAM MENGGUNAKAN METODE WALK TEST - Nurrahman, Winaldi; Zainuddin, Abdullah; yadnya, made sutha (Jurusan Teknik Elektro Fakultas Teknik Universitas Mataram, 2023)
Testing the signal power level is an important element to determine the classification of the signal power level in the measurement area by taking into account the standard signal reception parameters from the provider used. In this study, the signal power level was measured for indoor and outdoor conditions for Telkomsel and XL providers, as well as a statistical analysis of the results of path loss measurements at a working frequency of 2.1 GHz. This study aims to determine a good location for accessing the internet based on the results of measuring the signal power level value, so that from the signal power level mapping results obtained, the indoor provider XL condition value with the normal location category has an average signal power level of -90 dBm and the XL provider outdoor condition with the good category has an average power level of -80 dBm. In indoor conditions, Telkomsel providers are in the medium category with an average signal power level of -90 dBm, and in outdoor locations, Telkomsel providers are in the good, medium, and bad categories with power level values of -110 to -80.